Avaliar o quê? Os vários sentidos de efetividade no campo de estudos da participação - Martelli, Carla Giani [UNESP]; Coelho, Rony (FapUNIFESP (SciELO), 2021)
The main purpose of this article is to advance in the understanding of the term effectiveness that has been used to evaluate the results produced by participatory institutions. The literature review and the research into a corpus of 71 papers on the effectiveness of participation, presented in four editions of the “International Meeting Participation, Democracy and Public Policies”, show the multiplicity of meanings which the term effectiveness carries. We argue that the papers addressing this issue should define with accuracy what they intend to assess, as the conclusions of the participatory spaces validity and the necessary incentive to their continuity depend on the clarity of the evaluation object.
Evaluate what? The various meanings of effectiveness in the field of participation studies
¿Evaluar qué? Los distintos significados de la eficacia en el campo de los estudios de participación
Keywords: avaliação; efectividad; efetividade; effectiveness; efficacité; evaluación; evaluation; instituciones participativas; instituições participativas; institutions participatives; participación; participation; participatory institutions; participação; politique publique; política pública; public policy; évaluation